Disposisi Matematis dan Dampak Learning Cycle 7E terhadap Kemampuan Pemecahan Masalah dalam Matematika - Yustikarinda, Ananda Nadhifah; Widodo, Suryo; Katminingsih, Yuni (CV. AFDIFAL MAJU BERKAH, 2024)
The ability of Indonesian students to solve mathematical problems remains moderately low, according to PISA 2022 results. Even the desire and interest to learn mathematics are still relatively low. Hence, this study will determine the impact of the Learning Cycle 7E acquiring model on problem-solving abilities in relation to understudies' mathematical disposition. The procedure used in this assessment is quantitative. A quasi-experimental design was used for this study. The order picked in this experiment is the One Group Pretest-Posttest. The testing design in this review was a cluster random sampling method and got 31 students of 10th class SMAN 3 Kota Kediri. The data assortment process utilized a mathematical disposition survey and a trial of problem-solving abilities. In testing the hypothesis, the Wilcoxon Test result is 0.000 < 0.05 which shows that the Learning Cycle 7E learning model has an effect on students' mathematical problem-solving ability, and the Kruskal-Wallis Test result is 0.972 > 0.05 which shows that there is no difference in mathematical problem-solving ability between students with high, medium, and low mathematical disposition. So, the result of this study is that the 7E Learning Cycle learning model altogether influences problem-solving abilities and is powerful for all understudies' mathematical disposition levels.